IN THE CASE OF LOW BACK PAIN LUMBOSACRAL EXAMINATION IN PANDAN ARANG HOSPITAL - Dyah Ayu Puspitaningtyas; Silvi Nugraeni; Yuni Purwanti Hastuti (Medical Imaging and Radiation Protection Research Journal, 2022)
AP (Antero Posterior), Lateral and Oblique are lumbar projection that used in radiology for low back pain. In Pandan Arang Boyolali Hospital, central ray in lateral projection did not use angle for examination. In literature, always used an angle for lateral projection. Aim of this study is to knowing radiology examination of LBP and reason of lateral projection without angle. This research is used case study with data collection from observation, study literature and interview. Based on results, lumbar examination in Pandan Arang Boyolali Hospital used AP, Oblique and Lateral with perpendicular for central ray. Purpose lateral projection without angle is does required an angle because patient pelvic and thorax is not too wide.